Knowledge Engineering and Semantic Web : 6th International Conference, KESW 2015, Moscow, Russia, September 30 - October 2, 2015, Proceedings - Klinov, Pavel; Mouromtsev, Dmitry; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 6th Conference on Knowledge Engineering and the Semantic Web, KESW 2015, held in Moscow, Russia, in September/October 2015. The 17 revised full papers presented together with 6 short system descriptions were carefully reviewed and selected from 35 submissions. The papers address research issues related to semantic web, linked data, ontologies, natural language processing, knowledge representation.
Keywords: Information storage and retrieva; Artificial intelligence; Database management; Information Storage and Retrieval; Artificial Intelligence; Database Management